Social support, Spiritual well-being and Life satisfaction of Cancer patients - Abid, Shumaila; Bajwa, Ruqia Safdar (Journal of Pakistan Psychiatric Society, 2020)
Objective: To check the association of social support, spiritual well-being and life satisfaction among cancer patients. Study Design: It was a correlational study. Place and Duration of Study: The study was completed in three months from 2nd February 2018- 30th April 2018. The sample was from Nishtar Hospital, Multan (MINAR Multan). Subjects and Method: Purposive sampling was used to collect 100 cancer patients. Interpersonal Support Evaluation List 12, Spirituality Index of well-being and Satisfaction with Life scale were used to measure the degree of social support, spiritual well-being and life satisfaction in cancer patients. Results: The results indicated significant positive correlation between spiritual well-being and life satisfaction. There is also found a correlation in social support and life satisfaction. However, results also indicated that males have more social support as compare to females. Conclusion: There is found association of social support, spiritual well-being and life satisfaction in cancer patients